PENGARUH PENGGUNAAN VIDEO PEMBELAJARAN YOUTUBE KIDS UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was motivated by the low learning motivation of fifth-grade students at SD Negeri 1 Mastur, which was caused by monotonous, teacher-centered learning. One proposed solution is the use of YouTube Kids, an application that provides child-friendly and visually engaging educational content. The purpose of this study was to examine the effect of using YouTube Kids learning videos on students' learning motivation. The research employed a quantitative approach with a pre-experimental design, namely the One Group Pretest-Posttest Design. The subjects were 22 fifth-grade students selected through purposive sampling. The research instrument was a learning motivation questionnaire with a Likert scale, tested for validity and reliability. The research stages included administering a pretest, applying the treatment using YouTube Kids videos, and conducting a posttest with questionnaires. Data were analyzed using descriptive statistics and inferential statistics with a One Sample t-Test at a 0.05 significance level. The results showed that the average score of students' learning motivation increased to 70.82 with a standard deviation of 2.86, categorized as "very good." The t-test result was 9.556 with a significance value of 0.000 (<0.05), indicating that the use of YouTube Kids videos significantly improved learning motivation. Therefore, YouTube Kids can serve as an effective alternative medium to create interactive, enjoyable, and age-appropriate learning for elementary students.